2021
DOI: 10.21064/winrs.2021.0.1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the standard of living on the reproductive behavior of Russians: gender aspect

Abstract: The relevance of the study of the impact of living standards on the reproductive behavior of men and women is due to the complexity of the demographic situation at the national level, the inconsistency of the reproductive behavior of Russians, the need to develop predictive hypotheses of fertility, as well as identify institutional solutions that can be used to develop new measures in the framework of state programs to increase the birth rate in the Russian Federation. The empirical basis of the study is data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…Some articles point to an inverse correlation between the NEB and the income of individuals and households (Arkhan gelskiy et al, 2021;Turner, Robbins, 2023), and others have revealed correlations of different directions when men are compared with women (Fieder, Huber, 2022); it has also been noted that after the division of a cohort into subgroups by income level, the direction of the correlation changes (Co hen et al, 2013;Arkhangelskiy et al, 2021). Demographers pay special attention to the analysis of correlations between the birth rate and educational attainment.…”
Section: Demographic and Anthropometric Studiesmentioning
confidence: 99%
“…Some articles point to an inverse correlation between the NEB and the income of individuals and households (Arkhan gelskiy et al, 2021;Turner, Robbins, 2023), and others have revealed correlations of different directions when men are compared with women (Fieder, Huber, 2022); it has also been noted that after the division of a cohort into subgroups by income level, the direction of the correlation changes (Co hen et al, 2013;Arkhangelskiy et al, 2021). Demographers pay special attention to the analysis of correlations between the birth rate and educational attainment.…”
Section: Demographic and Anthropometric Studiesmentioning
confidence: 99%
“…В настоящее время репродуктивное поведение рассматривается как целостная система, основные компоненты которой -потребность в определенном количестве детей, репродуктивные нормы, принятые в разных социальных группах, репродуктивные установки и мотивация [1].…”
Section: Introductionunclassified